Reception of the «mimetic theory» of René Girard in the work of Peter Sloterdijk - Parrilla, Desiderio (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The mimetic hypothesis is an anthropological theory formulated by the anthropologist René Girard according to which the essence of human desire is characterized by a paradoxical and ambivalent imitation, generating effects of opposite sign. The philosopher Peter Sloterdijk has developed his famous «spherology» from the basis of this anthropological hypothesis. In fact, he not only used it on his phenomenology of affective space but also his criticism of psychoanalysis and his analysis of the post-industrial mass society. In this article we will discuss the main points of agreement and opposition between both authors.